PENGARUH GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWA JURUSAN EKONOMI ISLAM UIN SUMATERA UTARA - Syakhilah, Ade Fahdiya; Fadilah, Tasya; Lestari, Dini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The cause of the main problem in humans who behave consumptively is someone who cannot control themselves because of their inability to manage themselves properly with a way of life that needs to follow the latest fashions. The hedonic lifestyle of students has a favorable impact on consumer conduct. The information used in this research was gathered by sending questionnaires to respondents; this research approach employs quantitative approaches. The basic regression the data was examined using analysis. As stated by studies done on pupils at the Islamic Economics Department of UINSU by providing questionnaires regarding lifestyle's impact on consumption patterns, the author draws the conclusion that lifestyle affects the purchasing habits of UINSU students in the Islamic Economics Department. This is evidenced by the Ho is rejected but Ha is approved, according to the t test findings, which show a sig. value for the influence of variable X on Y of 0.000 <0.05 and a t count of 10.754> t table 1.984. Thus, it may be claimed that variable X significantly influences (lifestyle) and variable Y (consumptive behavior).